Using Assistive Technology in Teaching Students with Disabilities - Salim Alhazmi, Huda (International Journal of Psychosocial Rehabilitation, 2024)
This paper was written to expose the meaning, benefits, and answer in what ways do laws,regulations, resources, district practices, and theoretical understandings of disability andspecial education influence accessibility and decision- making for students with disabilities inthe area of assistive technology (AT)? The paper discussed promotes and detracts fromunderstanding AT in schools and evidenced-based practices to implement AT. It pointed outthe potential short term and long-term impact on learners with disabilities of utilizingconcepts from WATI, Quality Indicators of AT, the assistive technology continuum (highlow tech), and the SETT Framework. It provided implications of influences (procedures,practices, resources, cost/funding, referral, professional development, attitudes/beliefs) onincorporating assistive technology in schools. It concluded that recommendations for how toaddress possible obstacles that may influence the implementation of AT in the IEP